Above-ground biomass equations for birch (Betula pubescens Ehrh.) and pedunculate oak (Quercus robur L.) in north western Spain - Gómez-García, Esteban; Crecente-Campo, Felipe; Diéguez-Aranda, Ulises (Instituto de Ecología, A.C., 2013)
The aim of this study was to develop models for above-ground biomass estimation for birch(Betula pubescens Ehrh.) and pedunculate oak (Quercus robur L.) in Galicia (northwest of Spain). Datafrom a destructive sampling of 50 birch trees and 50 pedunculate oak trees, that provided total dry biomassweight and dry biomass weight by components: wood, bark, branches over 2 cm, branchesbetween 0,5 cm and 2 cm, branches under 2 cm, and leaves, was used. Different models were fitted foreach above-ground component and the best of them was chosen in a first step. All the models wererefitted simultaneously by use of Nonlinear Seemingly Unrelated Regressions (NSUR) to ensure theadditivity of the biomass equations. Weighted regression was necessary to correct the heterocedasticityof residuals. Not serious problems with multicollineality were observed. Finally, a system of seven equationsfor the different above-ground biomass components, and for the total biomass, was obtained for each species. These equations explainedat least 79% of the observed variability.For total biomass the equations explained98% and 97% of the observed variabilityfor birch and oak, respectively. The developedbiomass equations are recommendedin substitution of the existingregional biomass equations.